1984
DOI: 10.1136/ard.43.2.200
|View full text |Cite
|
Sign up to set email alerts
|

Report on chloroquine and dapsone in the treatment of rheumatoid arthritis: a 6-month comparative study.

Abstract: SUMMARY A controlled study compared 6 months' treatment of 60 patients with rheumatoid arthritis (RA). Halfwere randomly allocated to treatment with chloroquine 250 mg daily, the other half dapsone 100 mg daily (50 mg/day for the first 7 days) following a one-month run-in assessment period. All patients had active or progressing disease. Both treatment groups showed significant improvement in morning stiffness, number of painful joints, pain scores, Ritchie index, and proximal interphalangeal joint size, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…Nevertheless they both appear to produce significant clinical improvement in rheumatoid patients [19,20,21,22,28]. High doses of dapsone (100-150 mg/kg) failed to have any therapeutic effect on adjuvant arthritis in rats [29]; some activity was observed with a prophylactic schedule but this may have been due to gross toxicity of the compound.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Nevertheless they both appear to produce significant clinical improvement in rheumatoid patients [19,20,21,22,28]. High doses of dapsone (100-150 mg/kg) failed to have any therapeutic effect on adjuvant arthritis in rats [29]; some activity was observed with a prophylactic schedule but this may have been due to gross toxicity of the compound.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, we have investigated the activity of the orally active gold compound auranofin and two drugs which are being used increasingly for the treatment of rheumatoid arthritis, namely dapsone and sulphasalazine [19,20,21,22]. Two cytotoxic agents, azathioprine and methotrexate, have also been examined.…”
Section: Introductionmentioning
confidence: 99%
“…While elevation of liver enzyme levels accounted for no dropouts in 5 of the 7 trials we used (16)(17)(18)(19)(20) and accounted for only 1 dropout in one other trial (21), it was an important cause of dropout in the trial conducted by the CSSRD group (22). In that trial, liver enzyme elevations that were greater than twice the normal level dictated a patient's withdrawal from the study; this occurred in 18 of the 95 patients randomized to receive MTX.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have indicated the beneficial effects of antimalarials in rheumatoid arthritis 25–31 . Despite a low incidence of toxicity, 7,32 the long‐term drug survival rates have been low with anti‐malarials.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, chloroquine was found to be more effective than hydroxychloroquine 32,34 . Indeed, efficacy of chloroquine had been demonstrated in a few studies 27,29–31,35–40 . In one of these studies, chloroquine was found to be as effective as cyclosporin A 29 .…”
Section: Discussionmentioning
confidence: 99%